2014
DOI: 10.14737/journal.aavs/2014/2.4s.33.41
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Spread of Avian Influenza H5N1 Viruses

Abstract: The Asian lineage of H5N1 avian influenza virus emerged from geese (A/Goose/Guangdong/1/96) in China in 1996, and is continuing its spread infecting domestic poultry, other birds and sporadic infection to humans revealing its pandemic potential. Since late 2003, H5N1 virus has been reported over 60 counties in Asia, Europe and Africa killing millions of poultry and infected humans in 16 countries with a total of 650 confirmed cases including 386 fatal have been reported to WHO. Spread of H5N1 virus has been li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Even though human infection with HPAI H5 is relatively rare, when it does occur, the case fatality rate is high. From 2003 to 2014, 667 human cases have been identified, of which 58.9% were fatal . Although there is no evidence of sustained human‐to‐human transmission, the rapid emergence of novel strains of H5 viruses from animal reservoirs combined with the sporadic human infections indicates a high risk for pandemic HPAI H5 emergence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though human infection with HPAI H5 is relatively rare, when it does occur, the case fatality rate is high. From 2003 to 2014, 667 human cases have been identified, of which 58.9% were fatal . Although there is no evidence of sustained human‐to‐human transmission, the rapid emergence of novel strains of H5 viruses from animal reservoirs combined with the sporadic human infections indicates a high risk for pandemic HPAI H5 emergence.…”
Section: Introductionmentioning
confidence: 99%
“…From 2003 to 2014, 667 human cases have been identified, of which 58.9% were fatal. 13 Although there is no evidence of sustained human-to-human transmission, the rapid emergence of novel strains of H5 viruses from animal reservoirs combined with the sporadic human infections indicates a high risk for pandemic HPAI H5 emergence. Two recent studies independently demonstrated that as few as three to five mutations in HPAI H5N1 viruses could allow for the effective aerosol transmission between ferrets.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, long-distance transmission of some Gs/GD lineage H5Nx viruses by migratory birds had resulted in global HPAI outbreaks. A large outbreak of clade 2.2 H5N1 virus occurred in migratory waterfowl at Qinghai Lake, China, in 2005 and subsequently spread across Asia and into Europe ( Tosh et al. 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the period 2004–2014, the virus was introduced in more than 60 countries and in almost all cases, the virus did not persist. However, due to specific conditions in poultry production and value chain systems, and/or limited veterinary resources, the disease has remained endemic or recurrent in China, Viet Nam, Indonesia, Egypt, Bangladesh and Nepal 3 4 .…”
mentioning
confidence: 99%